Considering Proximal Urea Cycle Disorders in Expanded Newborn Screening - Tania Vasquez-Loarte; John D. Thompson; J. Lawrence Merritt (MDPI AG, 2020)
Proximal urea cycle disorders (PUCDs) have adverse outcomes such as intellectual disability and death, which may benefit from newborn screening (NBS) through early detection and prevention with early treatment. Ornithine transcarbamylase deficiency (OTCD) and carbamoyl phosphate synthetase 1 deficiency (CPS1D) are screened in six and eight states in the United States. We analyzed current evidence to see if it supports inclusion of PUCDs in the NBS panels based upon prevention potential, medical, diagnostic, treatment, and public health rationales. A literature review was performed in PubMed using MESH terms for OTCD, CPS1D, and NAGSD. A systematic review was performed in the hallmark of NBS inclusion criteria. We reviewed 31 articles. Molecular and biochemical diagnosis is available to provide diagnostic evidence. Untreated PUCDs have a significant burden with considerable developmental delay and mortality that may improve with early treatment. Tandem mass spectrometry can be used for NBS for PUCDs; however, citrulline and glutamine alone are not specific. Medical treatments currently available for PUCDs meet existing medical, diagnostic, treatment, and public health rationales. Improvement in NBS algorithms to increase sensitivity and specificity will allow earlier diagnosis and treatment to potentially improve disability and mortality rates.